Investigating the effects of laryngotracheal stenosis on upper airway aerodynamics - Cheng, Tracy; Carpenter, David; Cohen, Seth; Witsell, David; Frank‐Ito, Dennis O. (The Laryngoscope, 2018)
Objective Very little is known about the impact of laryngotracheal stenosis (LTS) on inspiratory airflow and resistance, especially in air hunger states. This study investigates the effect of LTS on airway resistance and volumetric flow across three different inspiratory pressures. Methods Head‐and‐neck computed tomography scans of 11 subjects from 2010 to 2016 were collected. Three‐dimensional reconstructions of the upper airway from the nostrils to carina, including the oral cavity, were created for one subject with a normal airway and for 10 patients with LTS. Airflow simulations were conducted using computational fluid dynamics modeling at three different inspiratory pressures (10, 25, 40 pascals [Pa]) for all subjects under two scenarios: 1) inspiration through nostrils only (MC), and 2) through both nostrils and mouth (MO). Results Volumetric flows in the normal subject at the three inspiratory pressures were considerably higher (MC: 11.8–26.1 L/min; MO: 17.2–36.9 L/min) compared to those in LTS (MC: 2.86–6.75 L/min; MO: 4.11–9.00 L/min). Airway resistances in the normal subject were 0.051 to 0.092 pascal seconds per milliliter (Pa.s)/mL (MC) and 0.035–0.065 Pa.s/mL (MO), which were approximately tenfold lower than those of subjects with LTS: 0.39 to 0.89 Pa.s/mL (MC) and 0.45 to 0.84 Pa.s/mL (MO). Furthermore, subjects with glottic stenosis had the greatest resistance, whereas subjects with subglottic stenosis had the greatest variability in resistance. Subjects with tracheal stenosis had the lowest resistance. Conclusion This pilot study demonstrates that LTS increases resistance and decreases airflow. Mouth breathing significantly improved airflow and resistance but cannot completely compensate for the effects of stenosis. Furthermore, location of stenosis appears to modulate the effect of the stenosis on resistance differentially. Level of Evidence NA. Laryngoscope, 128:E141–E149, 2018